Idiolect in Digital Communication: A Sociolinguistic Study of the Instagram Account @adindafala - Anggi Triandana; Siti Fitriah; Aprilia Kartika Putri; Yoga Mestika Putra; Ulil Amri (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines the forms and functions of idiolect on the Instagram account @adindafala from a sociolinguistic perspective. The focus of the study is directed toward the use of distinctive language that reflects the speaker’s identity in digital communication. This research employs a qualitative descriptive method, with data sources consisting of captions and stories posted on the Instagram account @adindafala. The data were collected through observation and documentation techniques, then analysed by identifying the forms of idiolect and the language functions used by the speaker. The results of the study indicate that the idiolect found on the Instagram account @adindafala is manifested through the use of code-mixing, phonological changes, regional language interference, slang, abbreviations, language play, and graphological variations. These forms demonstrate a tendency toward the use of creative and communicative nonstandard language in social media. In addition, personal and representational functions were identified in the speaker’s language use. The personal function is reflected through the use of humorous, expressive, casual, and nonstandard language to describe the speaker’s daily experiences, while the representational function is used to convey information related to the speaker’s activities and situations. The findings of this study show that idiolect on social media serves as a form of linguistic expression influenced by digital communication culture and interlanguage interaction.